Role of microclimate in management of yellow rust (Puccinia striformis f sp tritici) of wheat (Triticum aestivum) under Ludhiana conditions - SANDHU, SARABJOT KAUR; DHALIWAL, L K; PANNU, P P S (The Indian Journal of Agricultural Sciences, 2016)
The field experiment was conducted during rabi seasons of 2012-13 and 2013-14 at the Research Farm, School of Climate Change and Agricultural Meteorology, PAU, Ludhiana. Wheat (Triticum aestivum L.) varieties HD 2967, PBW 550 and PBW 343 were sown under two row direction, viz. North-South (N-S) and East-West (E-W). Yellow rust (Puccinia striformis f sp tritci) severity and incidence was recorded at weekly intervals. Disease severity index was higher (100%) during rabi 2012-13 as compared to 2013-14 (91%). Among different row direction the disease severity was higher under N-S row direction as compared to E-W row direction during both the years. Area under disease progress curve (AUDPC) was maximum in PBW 343 sown under N-S row direction as compared to other treatments. Among three varieties HD 2967 was highly resistant to yellow rust as it showed zero AUDPC. Highly significant value of R2 (0.91 and 0.90) was found when maximum meteorological parameters were combined in PBW 343 and PBW 550, respectively. Relationships were developed between microclimatic parameters, viz. canopy temperature and relative humidity. Analysis of these relationships indicated that disease and microclimatic parameters were interrelated. Higher R2 values of Humid Thermal Ratio (HTR), Special Humid Thermal Ratio (SHTR) and disease severity indicated that HTR and SHTR can be used as a disease predictor.